2021
DOI: 10.1038/s41598-021-92845-1
|View full text |Cite
|
Sign up to set email alerts
|

Blue light directly modulates the quorum network in the human pathogen Acinetobacter baumannii

Abstract: Quorum sensing modulates bacterial collective behaviors including biofilm formation, motility and virulence in the important human pathogen Acinetobacter baumannii. Disruption of quorum sensing has emerged as a promising strategy with important therapeutic potential. In this work, we show that light modulates the production of acyl-homoserine lactones (AHLs), which were produced in higher levels in the dark than under blue light at environmental temperatures, a response that depends on the AHL synthase, AbaI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…Particularly, we have accumulated a large amount of evidence about the light signal transduction and physiological responses at moderate temperatures such as 23°C, which are mainly but not only governed by the blue light using FAD (BLUF)-type photoreceptor BlsA 1,3−10 . We have also shown that A. baumannii responds to light at 37°C modulating virulence in an epithelial infection model using human keratinocytes in culture 7 , as well as quorum sensing 10 , through a BlsA-independent mechanism 7,10 . However, the light signal perception and transduction components operating at this temperature were not yet identi ed.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Particularly, we have accumulated a large amount of evidence about the light signal transduction and physiological responses at moderate temperatures such as 23°C, which are mainly but not only governed by the blue light using FAD (BLUF)-type photoreceptor BlsA 1,3−10 . We have also shown that A. baumannii responds to light at 37°C modulating virulence in an epithelial infection model using human keratinocytes in culture 7 , as well as quorum sensing 10 , through a BlsA-independent mechanism 7,10 . However, the light signal perception and transduction components operating at this temperature were not yet identi ed.…”
Section: Introductionmentioning
confidence: 74%
“…Blue light treatments. Blue light treatments were performed as described in our previous studies [1][2][3][4][6][7][8][9][10]32 . Brie y, cells were incubated for 24 hours (or else as speci ed) at 37°C in the dark or under blue light emitted by 9-light-emitting diode (LED) arrays, with an intensity of 6 to 10 µmol photons/m 2 /s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, we have accumulated a large amount of evidence about the light signal transduction and physiological responses at moderate temperatures such as 23 °C, which are mainly but not only governed by the blue light using FAD (BLUF)-type photoreceptor BlsA 1 11 . We have also shown that A. baumannii responds to light at 37 °C modulating virulence in an epithelial infection model using human keratinocytes in culture 11 , as well as quorum sensing 10 , through a BlsA-independent mechanism 10 , 11 . However, the light signal perception and transduction components operating at this temperature were not yet identified.…”
Section: Introductionmentioning
confidence: 76%
“…From analyses of ours as well as other researchers’ data 20 , we observed that the BfmRS system and light integrate signals into the same pathways in A. baumannii. In fact, BfmR/S and light regulate catalase production 3 , 23 ; the phenylacetic acid degradation pathway 4 , 20 ; the acetoin catabolic pathway 9 ; trehalose biosynthesis; pellicle formation 4 , 16 , and biofilm formation 4 , 14 ; as well as expression of the Acinetobactin operon 8 , genes coding for the AdeABC efflux pump 7 , 20 , genes coding for the efflux pump EmrAB 3 , 20 , components of the quorum sensing machinery such as abaI 10 , 20 , fimbria 3 , 20 and the T6SS system 16 . Furthermore, it has been shown that BfmR interacts with BlsA mostly in the dark 29 .…”
Section: Introductionmentioning
confidence: 99%